Ichthyotoxicity of the Dinoflagellate Karlodinium veneficum in Response to Changes in Seawater pH - Müller, Marius N.; Dorantes-Aranda, Juan José; Seger, Andreas; Botana, Marina T.; Brandini, Frederico P.; Hallegraeff, Gustaaf M. (Frontiers in Marine Science, 2019)
The ichthyotoxic dinoflagellate Karlodinium veneficum has a worldwide distribution and produces highly potent lytic toxins (karlotoxins) that have been associated with massive fish kill events in coastal environments. The capacity of K. veneficum to gain energy from photosynthesis as well as phagotrophy enables cellular maintenance, growth and dispersal under a broad range of environmental conditions. Coastal ecosystems are highly dynamic in light of the prevailing physicochemical conditions, such as seawater carbonate speciation (CO2, HCO3- and CO32-) and pH. Here, we monitored the growth rate and ichthyotoxicity of K. veneficum in response to a seawater pH gradient. Karlodinium veneficum exhibited a significant linear reduction in growth rate with elevated seawater acidity (pH(total scale) from 8.05 to 7.50). Ichthyotoxicity was assessed by exposing fish gill cells to K. veneficum extracts and subsequent quantification of gill cell viability via resorufin fluorescence. Extracts of K. veneficum indicated increased toxicity when derived from elevated pH treatments. The variation in growth rate and toxin production per cell in regard to seawater pH implies that (1) future alteration of seawater carbonate speciation, due to anthropogenic ocean acidification, may negatively influence physiological performance and ecosystem interactions of K. veneficum and (2) elevated seawater pH values (> 8.0) represent favourable conditions for K. veneficum growth and toxicity. This suggests that prey of K. veneficum may be exposed to increased karlotoxin concentrations at conditions when nutrients are scarce and seawater pH has been elevated due to high photosynthetic activity from prior autotrophic phytoplankton blooms.